2004
DOI: 10.1634/theoncologist.9-6-673
|View full text |Cite
|
Sign up to set email alerts
|

Granisetron: An Update on its Clinical Use in the Management of Nausea and Vomiting

Abstract: ABSTRACTchemotherapy-induced, radiation-induced, and postoperative nausea and vomiting, and also reviews its use in special patient populations. Granisetron is a potent and highly selective 5-HT 3 -receptor antagonist that has little or no affinity for other receptors, a characteristic that is thought to underlie the favorable side-effect and safety profiles of this agent. Extensive clinical trial data have shown granisetron to be an effective and well-tolerated agent for the treatment of nausea and vomiting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 97 publications
0
60
0
Order By: Relevance
“…16 Granisetron is not cardiotoxic in dosages lower than 300 mg/kg. 16,17 The recommended dose of granisetron is 40 mg/kg. In more than 60% of patients, this dose prevents emesis for 24 hours post chemotherapy or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Granisetron is not cardiotoxic in dosages lower than 300 mg/kg. 16,17 The recommended dose of granisetron is 40 mg/kg. In more than 60% of patients, this dose prevents emesis for 24 hours post chemotherapy or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In more than 60% of patients, this dose prevents emesis for 24 hours post chemotherapy or radiation therapy. 17 Side effects have been noted in a small percentage of patients; the most common is headache, which occurs in 15% of cases. The recommended dose of granisetron has proved safe and effective in children.…”
Section: Discussionmentioning
confidence: 99%
“…The N-methyl group in the axial conformation is thought to be the pharmacophore for TAs [21]. Additionally, the granatane ring system provides the semisynthetic intermediate for the potent antiemetic agents Dolasteron and Granisetron, which are serotonin 5-HT 3 receptor agonists [22,23]. These compounds are used as medicines to prevent acute nausea in patients undergoing chemotherapy and radiotherapy for the treatment of cancer [24].…”
Section: Similarities and Differences In Medicinal Propertiesmentioning
confidence: 99%
“…Various data from extensive clinical trial and follow-up showed that granisetron is a very effective and well tolerated agent for the prevention of nausea and vomiting in the oncology patiens 14 . There were only a few studies carried out in children addressing the prevention of chemotherapy related nausea and emesis and they had reported that despite all other improvement in treating CRNV, no standard pediatric antiemetic drug had yet been established 15 .…”
Section: Introductionmentioning
confidence: 99%